2020
DOI: 10.3389/fped.2020.00388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Metrics During Pediatric Rhesus Macaque Development

Abstract: Background: Clinical measurements commonly used to evaluate overall health of laboratory animals including complete blood count, serum chemistry, weight, and immunophenotyping, differ with respect to age, development, and environment. This report provides comprehensive clinical and immunological reference ranges for pediatric rhesus macaques over the first year of life. Methods: We collected and analyzed blood samples from 151 healthy rhesus macaques, aged 0-55 weeks, and compared mother-reared infants to two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…After infection, the neonate exhibited asymptomatic clinical signs and had no major changes in temperature, oxygen saturation, respiratory rate, and heart rate ( Supplementary Figure S1A ). The newborn weighed around 450 g at birth and gained weight throughout the study, consistent with expected standards ( 45 ) ( Supplementary Figure S1B ).…”
Section: Resultssupporting
confidence: 80%
“…After infection, the neonate exhibited asymptomatic clinical signs and had no major changes in temperature, oxygen saturation, respiratory rate, and heart rate ( Supplementary Figure S1A ). The newborn weighed around 450 g at birth and gained weight throughout the study, consistent with expected standards ( 45 ) ( Supplementary Figure S1B ).…”
Section: Resultssupporting
confidence: 80%
“…Although systems vaccinology approaches have already been used in human cohorts of aged individuals [63,221,222], high-throughput characterization of vaccine-induced responses in children are still rare [9,223] and awaited for newborns [224]. Importantly, NHPs provide a highly relevant pediatric model to test vaccine efficacy, as they share many similarities with humans in terms of immune system development [225][226][227][228].…”
Section: Stepping Up Personalized Vaccinologymentioning
confidence: 99%
“…It is known that these reference values are affected by various parameters such as age, sex, fasting, sedation, or methods of restraint [3]. Some studies have either reported data of purpose-bred or wild-caught animals of different species [9,10]. However, no reports are available that compare and analyze reference values for hematological and biochemical parameters in inhouse and wild-sourced Indian rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%